Bicycle as a New Tourism Trend and Transportation in the New Normal - Rovena Dellova; Erica R. Bigoy; John Jeffrey G. Jogno; Ella Jane S. Joson; Mark Ardrin Monterola; Sophia Jamela T. Santos (International Journal of Applied Research in Tourism and Hospitality, 2022)
Bicycle tourism is booming in the tourism market and exists as a means of transportation in hundreds of cities around the world. However, in the Philippines, it was only popularized after the COVID-19 pandemic caused a transportation crisis and a massive decline in tourism growth. This qualitative study determines bicyclists’ perceptions, identified bicycling problems encountered, and explores bicycling opportunities in the new normal. The study utilized a phenomenological research design with data from virtual interviews with 10 bicyclists in Metro Manila. They were identified using purposive sampling and data saturation. The findings revealed that bicycle tourism is perceived as a sustainable activity that can promote and boost a destination’s local tourism. Meanwhile, using the bicycle as means of transportation is perceived as an efficient, affordable, and sustainable mode of active transportation and provides health benefits. It was also found to bring economic opportunities like job employment and became a catalyst for bicycle- related businesses to arise. Researchers concluded that bicycling would increase with these opportunities, This will pave the way for recovery, resulting in more sustainable tourism and transportation industry in the Philippines.